Comparision Deposit Formation On The Valve Diesel Engine Caused By Biodiesel And Petroleum Diesel Fuels - Maymuchar Maymuchar; Ismoyo Suro Waskito (Testing Center for Oil and Gas LEMIGAS, 2012)
Â The research on the infl uence of the biodiesel to the formation of deposits on the intake and exhaust valves diesel engine has been carried out by means analysis of merit rating. The fuels used on this study are FAME (B-100), a mixture of 50% (v)of FAME in diesel fuel 48 (B-50), and diesel fuel 48 (B-0). The objective of this research is to obtain data which represent the infl uence of the biodiesel to the formation of deposits on the intake and exhaust valve diesel engine. The test used a diesel engine driving 5 KVA generator which is operated for 100 hours with 1.000 Watt electrical load. The results of the study show that the use of either FAME or biodiesel as alternative fuel in the diesel engine generator 5 KVA has a positive effect on reducing the deposit on the intake and exhaust valves.